Peripheral nerve regeneration following scaffold-free conduit transplant of autologous dermal fibroblasts: a non-randomised safety and feasibility trial - Ikeguchi, Ryosuke; Aoyama, Tomoki; Noguchi, Takashi; Ushimaru, Mika; Amino, Yoko; Nakakura, Akiyoshi; Matsuyama, Noriko; Yoshida, Shiori; Nagai-Tanima, Momoko; Matsui, Keiko; Arai, Yasuyuki; Torii, Yoko; et al. (Communications medicine, 2024)
Background The use of Bio 3D nerve conduits is a promising approach for peripheral nerve reconstruction. This study aimed to assess their safety in three patients with peripheral nerve defects in their hands. Methods We describe a single institution, non-blinded, non-randomised control trial conducted at Kyoto University Hospital. Eligibility criteria included severed peripheral nerve injuries or a defect in the region distal to the wrist joint not caused by a congenital anomaly; a defect with a length of ≤20 mm in a nerve with a diameter ≤2 mm; failed results of sensory functional tests; ability to register in the protocol within 6 months from the day of injury; refusal of artificial nerve or autologous nerve transplantation; age 20–60 years; and willingness to participate and provide informed written consent. Six weeks before transplantation, skin was harvested, dermal fibroblasts were isolated and expanded, and Bio 3D nerve conduits were created using a Bio 3D printer. Bio 3D nerve conduits were transplanted into the patients’ nerve defects. The safety of Bio 3D nerve conduits in patients with a peripheral nerve injury in the distal part of the wrist joint were assessed over a 48-week period after transplantation. Results No adverse events related to the use of Bio 3D nerve conduits were observed in any patient, and all three patients completed the trial. Conclusions Bio 3D nerve conduits were successfully used for clinical nerve reconstruction without adverse events and are a possible treatment option for peripheral nerve injuries. Plain language summary Physical injuries often result in damage to nerves, for example, in the hands. Replacement of the nerve with nerves removed from elsewhere in the patient’s body is often the suggested treatment when the nerve is unable to repair itself. As an alternative to remove healthy nerve from elsewhere in the body, we used an adapted printer to create an artificial nerve equivalent from skin cells obtained from the patient’s skin. We reconstructed the nerves of three individual with nerve defects in their hands, and we found that the function of the nerve improved, and the people did not experience negative consequences. This approach could be used widely to repair damaged nerves. Ikeguchi et al. established nerve conduits from three patients’ dermal fibroblasts using a bioprinter and transplanted them back into the patients’ nerve defects. No adverse events occurred, and the nerves recovered following the transplant.